Behavior of the physical and mechanical properties of the concrete incorporating reed fiber into the mixture (Gaceta Técnica, 2024)
The objective of this study was to evaluate the behavior of the physical and mechanical properties of concrete by incorporating reed fiber into the mixture. For this purpose, it was proposed to add cane fiber to the dosage to analyze how this natural material modifies the concrete properties; Taking into account the possibility and openness of having alternative materials, an information search was carried out to analyze all the knowledge and information on the physical-mechanical properties, the latter validated by the California Bearing Ratio (CBR) that are presented in the different dosages of 0,0%; 0,8%; 1,2% and 1,6% reed fiber. As a result, it was obtained that the concrete pattern had a maximum dry density of 2,06 gr/cm³, an optimal moisture content of 3,43% and a CBR of 92% at a Penetration of 0,2” at 100% maximum dry density, and a CBR at 82% in a Penetration of 02” at 95% of maximum dry density. However, with the dosage of reed fiber of 0,8%, the results were a maximum dry density of 2,07gr/cm³, an optimal moisture content of 3,09% and a CBR of 97,8% in a Penetration of 0,2” at 100% maximum dry density, and a CBR at 84% at a Penetration of 0,2” at 95% maximum dry density. Finally, it is worth mentioning that the potential use of this material increases significantly compared to the standard sample, demonstrating physical and mechanical improvements
Keywords: reed fiber; CBR; dry density; sustainable concrete; durability of materials